ChemInform Abstract: Br2 as a Novel Lewis Acid Catalyst for Friedel—Crafts Alkylation of Indoles with α, β‐Unsaturated Ketones. Issue 27 (16th June 2016) - Liang, Deqiang; Li, Xiangguang; Zhang, Wanshun; Li, Yanni; Zhang, Mi; Cheng, Ping
Abstract: Under the catalysis of 3—10 mol% of Br2, the Michael addition proceeds with high efficiency and broad substrate scope to afford the corresponding β‐indolylketone derivatives.